The Efficacy of Oral Betamethasone versus Oral Prednisone in the Management of Acute Asthma - Iqbal, Arshad; Shamshad, Tanzeelah; Iqbal, Raghib; Liaquat, Fiza (Biological and Clinical Sciences Research Journal, 2025)
Acute asthma in children are a major cause of emergency department visits and hospital admissions. Objective: To compare the efficacy and safety of oral betamethasone versus oral prednisone in the management of acute asthma exacerbations in children aged 2 to 12 years. Methods: This randomized controlled trial was conducted at the Department of Pediatrics, Sheikh Zayed Hospital, Rahim Yar Khan from Oct 2024 to March 2025. A total of 166 children presenting to the emergency department with acute asthma exacerbations were enrolled using non-probability consecutive sampling. Participants were randomly assigned to receive either oral prednisone (n=83) or oral betamethasone (n=83). Results: The mean length of hospital stay was 47.6 ± 12.3 hours in the prednisone group and 49.9 ± 13.8 hours in the betamethasone group (p = 0.18). Persistence of symptoms occurred in 16.9% of the prednisone group and 20.5% of the betamethasone group (p = 0.54). Rates of ED revisits (12.0% vs. 14.5%), hospital readmissions (6.0% vs. 8.4%), and steroid-related side effects (9.6% vs. 7.2%) were similar between groups, with no statistically significant differences. Conclusion: It is concluded that oral betamethasone is as effective and safe as oral prednisone in treating acute asthma exacerbations in children. Given its pharmacokinetic profile, betamethasone may offer practical advantages in clinical settings, warranting further exploration in future studies.